Carbon dioxide gas selective separation composite membrane and preparation method thereof
Patent Information
- Application Number
- CN202311860602.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-12-29
AI Technical Summary
Mixed matrix membranes have low permeability and poor CO2 gas separation selectivity. Mixed matrix membranes prepared by direct blending have problems such as poor compatibility, poor mechanical properties and particle agglomeration, which affect the gas separation performance of the membrane.
A zeolite imidazole ester framework polycrystalline film was composited with a polymer. A precursor liquid was coated on a carrier by dip-coating thermal conversion and then heated and cooled to form a zeolite imidazole ester framework polycrystalline film. Subsequently, a polymer solution was coated on its surface to repair intercrystalline defects and form a composite film with a through-structure.
It improves the permeability and selectivity of CO2 gas, forms a continuous and dense composite membrane, has good separation performance, is simple to operate, has high repeatability, and is suitable for a variety of CO2 gas separation systems.
Smart Images

Figure CN117732276B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane materials, and more specifically, to a carbon dioxide gas selective separation composite membrane and its preparation method. Background Technology
[0002] Compared to chemical absorption, cryogenic distillation, and other methods, which suffer from high costs, large footprints, and high energy consumption, membrane separation technology is widely used in CO2 capture and separation due to its advantages such as simple operation, low energy consumption, small footprint, and high separation efficiency. Currently, membrane separation technology is applied to CO2 capture using three strategies: capturing and separating CO2 from syngas (H2 / CO2) after water-gas conversion before combustion; capturing and separating CO2 from flue gas (CO2 / N2) after combustion; and natural gas decarbonization (CO2 / CH4).
[0003] Membrane materials used for CO2 separation include polymer membranes, inorganic membranes, and mixed-matrix membranes. Among these, polymer membranes, in gas separation applications, struggle to overcome the Robeson upper limit due to a trade-off effect between permeability and selectivity. While inorganic membranes offer high permeability and selectivity, their lower mechanical strength, repeatability, and high cost hinder their industrial application. Mixed-matrix membranes, as a novel type of membrane material composed of inorganic materials and a polymer matrix, hold great potential in membrane separation technology and are expected to break through the Robeson upper limit of polymer membranes. However, most mixed-matrix membranes prepared by direct blending exhibit poor compatibility, poor mechanical properties, and particle agglomeration at high loading rates, thus affecting the membrane's gas separation performance. Furthermore, directly blended mixed-matrix membranes are typically thick, which is detrimental to gas transport and leads to reduced membrane permeability. Summary of the Invention
[0004] The problem to be solved by this invention is how to solve the problem of low permeability and poor selectivity of CO2 gas separation in mixed matrix membranes.
[0005] To address the aforementioned problems, the first aspect of this invention provides a carbon dioxide gas selective separation composite membrane. The carbon dioxide gas selective separation composite membrane comprises a zeolite imidazole ester framework polycrystalline membrane and a polymer. The polymer fills the intercrystalline defects on the membrane surface of the zeolite imidazole ester framework polycrystalline membrane. Because of the presence of the polymer, the intercrystalline defects of the polycrystalline membrane are repaired, and the thinner membrane layer increases CO2 permeability, resulting in excellent separation performance of the composite membrane.
[0006] A second aspect of the present invention provides a method for preparing the aforementioned carbon dioxide gas selective separation composite membrane, comprising the following steps:
[0007] S1: Preparation of zeolite imidazolium ester framework polycrystalline film;
[0008] S2: Activation of zeolite imidazole ester framework polycrystalline film;
[0009] S3: The polymer is filled into the intercrystalline defects on the surface of the activated zeolite imidazole ester framework polycrystalline membrane to obtain a carbon dioxide gas selective separation composite membrane.
[0010] The layer-by-layer composite process of this composite membrane includes: preparing a thin layer of inorganic filler with high bonding strength to the carrier using an dip-coating thermal conversion method; and coating with a polymer solution to construct a high-load organic-inorganic composite membrane. The layer-by-layer composite method can precisely control the interface structure between the inorganic filler thin layer and the support, as well as between the polymer and the composite membrane, forming a composite membrane with a through-structure, making the pores of the inorganic filler the main channels for molecular transmembrane transport.
[0011] In the preparation method of this invention, a precursor solution is coated onto a carrier using a dip-coating thermal conversion method, followed by heating, cooling, and activation of the carrier coated with the precursor solution to prepare a zeolite imidazolate framework polycrystalline membrane containing crystal grains; the zeolite imidazolate framework polycrystalline membrane obtained in step S1 is then activated. A polymer solution is then coated onto the surface of the zeolite imidazolate framework polycrystalline membrane obtained in step S2 to obtain a carbon dioxide gas selective separation composite membrane.
[0012] Preferably, step S3 includes the following steps:
[0013] S31: Mix the polymer with a polar solvent to obtain a polymer solution;
[0014] S32: The polymer solution is coated onto the surface of the activated zeolite imidazole ester framework polycrystalline membrane, and the polar solvent is removed by heating to obtain a selective separation composite membrane.
[0015] Further preferably, the polar solvent is N,N dimethylformamide or N,N dimethylacetamide.
[0016] Further preferably, the coating method can be selected from any one of dip coating, spin coating, dip coating, and spray coating.
[0017] Preferably, in step S31, the polymer has a mass fraction of 1% to 25% in the polar solvent.
[0018] As the most preferred embodiment, the polymer has a mass fraction of 4% to 15% in the polar solvent.
[0019] Preferably, in step S31, the polymer is selected from one or more of polysulfone, Pebax-2533, Pebax-1657, polyvinylpyrrolidone, self-polymerizing microporous polymer-1, polybenzimidazole, P84, polyethylene, polyether block polyamide, polymethyl methacrylate, polyethersulfone, PDMS, and polyimide.
[0020] As the most preferred option, the polymer is selected from one or more of polysulfone, Pebax-2533, Pebax-1657, polyethersulfone, PDMS, and polyimide.
[0021] Preferably, step S1 includes the following steps:
[0022] S11: Mix a metal salt, an organic ligand, a polar solvent, and water, wherein the organic ligand is one of imidazole-2-carboxaldehyde, 2-methylimidazolium, 4-methylimidazolium-5-carboxaldehyde, benzimidazole, 5-methylbenzimidazole, 2-aminobenzimidazole, 4,5-dichloroimidazolium, and 2-nitroimidazolium, and the metal salt is a zinc salt or a cobalt salt, to obtain a precursor solution;
[0023] S12: Coat the carrier with a precursor solution, heat and cool the carrier coated with the precursor solution at a temperature of 50-300℃ to obtain a zeolite imidazole ester framework polycrystalline film.
[0024] Further preferably, the polar solvent is N,N dimethylformamide or N,N dimethylacetamide.
[0025] Further preferably, the metal salt is selected from any one of zinc nitrate hexahydrate, zinc acetate dihydrate, or cobalt acetate tetrahydrate.
[0026] In the above reaction, after the precursor liquid is heated at high temperature, a large amount of reaction raw materials are uniformly covered on the surface of the carrier to nucleate and grow, forming a crystalline layer, and then forming a polycrystalline film of zeolite imidazole ester framework.
[0027] Preferably, in step S11, the molar ratio of the metal salt, organic ligand, polar solvent, and water is 1:(1-10):(20-600):(50-1200).
[0028] As the most preferred embodiment, the molar ratio of the metal salt, organic ligand, polar solvent and water is 1:(1-6):(50-150):(120-400).
[0029] Preferably, in step S12, the support is selected from one of α-Al2O3 support, γ-Al2O3 support, and TiO2 support.
[0030] Preferably, in step S2, the activation of the zeolite imidazole ester framework polycrystalline film includes the following steps: immersing the zeolite imidazole ester framework polycrystalline film in a volatile solvent for 0.5 to 5 hours, and then drying it to obtain the activated zeolite imidazole ester framework polycrystalline film.
[0031] Further preferably, the volatile solvent is selected from methanol, ethanol, acetone, acetonitrile, and chloroform.
[0032] A third aspect of the present invention provides an application of the aforementioned carbon dioxide gas selective separation membrane, namely, using the aforementioned carbon dioxide gas selective separation membrane for the efficient separation of carbon dioxide.
[0033] Preferably, the separation can be performed by separating carbon dioxide gas from a mixed gas, wherein the mixed gas is selected from any one of methane, nitrogen, and hydrogen, or a mixture of multiple gases with carbon dioxide.
[0034] The beneficial effects of this invention are as follows: The carbon dioxide selective separation composite membrane prepared by this invention has a thin and defect-free membrane layer. The pores of the inorganic filler serve as the main transport channels for molecular transmembrane transport, significantly improving the separation performance of the carbon dioxide selective separation composite membrane. The preparation method of this invention has the advantages of simple operation, high repeatability, and wide applicability. The carbon dioxide selective separation composite membrane is continuous, dense, and defect-free, with good organic-inorganic membrane layer compatibility. This composite membrane exhibits good separation performance in various CO2 gas separation systems. Furthermore, the use of polymer coating in this invention has been proven to be a method for repairing defects and improving selectivity, providing inspiration for the subsequent development of carbon dioxide selective separation composite membranes. Attached Figure Description
[0035] Figure 1 The X-ray diffraction characterization results of the zeolite imidazole ester framework polycrystalline film A3 and the selective separation composite film M3 prepared in Example 1 of the present invention are shown in the figure.
[0036] Figure 2 This is a scanning electron microscope (SEM) characterization result of the zeolite imidazole ester framework polycrystalline film A2 prepared in Example 1 of the present invention.
[0037] Figure 3 This is a scanning electron microscope (SEM) characterization result of the selective separation composite membrane M2 prepared in Example 1 of this invention.
[0038] Figure 4 This is a graph showing the single-component gas permeation test results of the selective separation composite membrane M3 prepared in Example 1 of this invention.
[0039] Figure 5The image shows the X-ray diffraction characterization results of the selective separation composite membranes M1-M4 prepared in Example 1 of this invention. Detailed Implementation
[0040] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation methods and typical parameters of the present invention, and are not intended to limit the parameter range described in the present invention. Reasonable variations derived therefrom are still within the protection scope of the claims of the present invention.
[0041] It should be noted that the endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0042] Unless otherwise specified, the selective separation of two-component mixed gases mentioned in this invention refers to the ratio of the permeability of the two gases; the gas permeability is the amount of gas passing through a unit membrane area (m²) per unit time (s) and unit pressure (Pa). 2 The amount of substance (mol) of the gas. In the specific embodiments of the present invention, both of the above parameters are measured according to the method in J. Membr. Sci. (2010, 354, 48-54.).
[0043] The present invention provides a method for preparing a carbon dioxide gas selective separation composite membrane, which combines the advantages of inorganic membranes and polymer membranes. The specific preparation steps are as follows:
[0044] S1: Mix a metal salt, an organic ligand, a polar solvent, and water. The organic ligand is one of imidazole-2-carboxaldehyde, 2-methylimidazolium, 4-methylimidazolium-5-carboxaldehyde, benzimidazole, 5-methylbenzimidazole, 2-aminobenzimidazole, 4,5-dichloroimidazolium, and 2-nitroimidazolium. The metal salt is a zinc salt or a cobalt salt. Obtain a precursor solution. Coat the precursor solution onto a support. Heat and cool the support coated with the precursor solution at a temperature of 50–300°C to obtain a zeolite imidazole ester framework polycrystalline film.
[0045] S2: Immerse the zeolite imidazole ester framework polycrystalline film in a volatile solvent for 0.5 to 5 hours, and then dry it to obtain the activated zeolite imidazole ester framework polycrystalline film.
[0046] S3: The polymer is mixed with a polar solvent to obtain a polymer solution, and the polymer solution is coated on the surface of the activated zeolite imidazole ester framework polycrystalline membrane. The polar solvent is removed by heating to obtain a carbon dioxide gas selective separation composite membrane.
[0047] In the above embodiments, the metal salt is a zinc salt (zinc nitrate hexahydrate or zinc acetate dihydrate) or a cobalt salt (cobalt acetate tetrahydrate).
[0048] In the above embodiments, the organic solvents were all N-dimethylformamide or N-dimethylacetamide.
[0049] In the above embodiments, the molar ratio of metal salt, organic ligand, polar solvent and water is 1:(1-6):(50-150):(120-400).
[0050] In the above embodiments, the support is selected from one of α-Al2O3 support, γ-Al2O3 support, and TiO2 support.
[0051] In the above embodiments, the polymer is selected from one or more of polysulfone, Pebax-2533, Pebax-1657, polyethersulfone, PDMS, and polyimide.
[0052] In the above embodiments, the polymer has a mass fraction of 4%-15% in the polar solvent.
[0053] In the above embodiments, the volatile solvent is selected from methanol, ethanol, acetonitrile, acetone, and chloroform.
[0054] The method for preparing the carbon dioxide gas selective separation composite membrane provided in this embodiment involves immersing a carrier in a precursor solution and subjecting it to high-temperature treatment. This causes the solvent in the carrier to evaporate rapidly, driving the precursor solution to flow from the inside of the carrier to the outside, where it crystallizes and transforms inside and outside the carrier to form a zeolite imidazole ester framework polycrystalline membrane. The specific heating temperature can be set to 50℃~300℃, preferably 200℃; the heating time is 5~60 minutes, preferably 15 minutes.
[0055] Products treated at high temperatures require solvent activation. In this embodiment of the invention, methanol is used as the activator to activate the crystallized film. Unless otherwise specified, the activation described in this specification refers to the conventional understanding of immersing the product to be activated in the activator for a period of time. For example, methanol activation in this embodiment refers to immersing the product to be activated in methanol for a specified time. The specified time is 0.5 to 5 hours, preferably 2 hours. Therefore, for the system of this invention, a suitable activation time can achieve the goal of removing residual polar solvents without damaging the product performance.
[0056] This embodiment provides a preferred implementation method: A zeolite imidazole organic framework precursor solution is coated onto the surface of a carrier, then dried at 200°C for 15 minutes. After naturally cooling to room temperature, the resulting product is activated with methanol for 2 hours, and then dried to obtain a polycrystalline membrane. The obtained product is coated with a polymer solution on its surface using a dip-coating method, and then heated under vacuum at 150°C for 24 hours to obtain a selective separation composite membrane. The precursor solution, by molar ratio, is a mixed solution containing 1 part Zn, 2 parts 2-methylimidazole, 72 parts N,N-dimethylformamide, and 185 parts deionized water.
[0057] In specific embodiments of the present invention, unless otherwise specified, ZIF refers to the conventionally understood zeolite imidazole ester skeleton material.
[0058] Example 1
[0059] Effect of ZIF-8 precursor solution concentration on ZIF-8 / PSF selective separation composite membrane
[0060] Preparation of ZIF-8 precursor solutions of different concentrations: Under the condition of constant solvent addition, the mass of metal salt and organic ligand was reduced to 1 / 2, 1 / 4 and 1 / 8 of the initial value in equal proportion. Then, 2-methylimidazole and zinc acetate dihydrate were dissolved in DMAc and deionized water. Finally, the zinc acetate dihydrate solution was added to the ligand solution and stirred in an ice bath until the solution was clear to obtain ZIF-8 precursor solutions with concentrations of 1U, 0.5U, 0.25U and 0.125U.
[0061] Preparation of ZIF-8 polycrystalline films with different precursor solution concentrations: Eight identical α-Al₂O₃ alumina supports (70 nm pore size) were immersed in precursor solutions of different concentrations for 30 seconds each, and then quickly transferred to a 200°C forced-air oven for 15 minutes, followed by natural cooling to room temperature. The ZIF-8 polycrystalline films were activated with methanol solvent for 2 hours and dried at room temperature. The resulting products were designated as A1, A2, A3, and A4, respectively.
[0062] Preparation of ZIF-8 / PSF selective separation composite membrane: A 5% PSF polymer solution was coated on the surface of products A1, A2, A3, and A4 by a dip-coating method. The membranes were then placed in a vacuum oven at 150°C and dried under vacuum for 24 hours. After cooling to room temperature, the resulting products were labeled as M1, M2, M3, and M4, respectively.
[0063] Characterization of ZIF-8 / PSF selective separation composite membranes: ZIF-8 polycrystalline membranes A1, A2, A3, A4 and ZIF-8 / PSF selective separation composite membranes M1, M2, M3, M4 with different precursor solution concentrations prepared above were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The separation selectivity and permeability of single-component and two-component gases were also measured. The XRD characterization results of 0.5U ZIF-8 polycrystalline membrane A3 and 0.5U ZIF-8 / 5% PSF selective separation composite membrane M3 are shown below. Figure 1 As shown; SEM characterization of the 0.25U ZIF-8 polycrystalline film A2 is as follows. Figure 2 As shown; SEM characterization of the 0.25U ZIF-8 / 5% PSF selective separation composite membrane M2 is as follows. Figure 3 As shown; the single-component gas permeation test of the 0.5U ZIF-8 / 5% PSF selective separation composite membrane M3 is as follows. Figure 4 As shown; X-ray diffraction characterization of ZIF-8 / PSF selective separation composite membranes M1-M4 is as follows. Figure 5 As shown.
[0064] from Figure 1 XRD characterization results for A3 and M3 show that the characteristic peaks of the 0.5U ZIF-8 polycrystalline film A3 and the 0.5U ZIF-8 / 5% PSF selective separation composite film M3, prepared by rapid thermal deposition, are consistent with the simulated data. From A2 ( Figure 2 ) and M2 ( Figure 3 SEM characterization results show that the polymer solution completely covers the surface of the ZIF-8 polycrystalline film, effectively repairing inter-film defects. From M3 ( Figure 4 The relationship between the gas permeability and the gas dynamic diameter shows that the gas permeability of M3 gradually decreases as the gas dynamic diameter increases. The permeability of CO2 is 1.6 × 10⁻⁶. -8 mol m -2 s -1 Pa -1 The ideal selectivities for CO2 / N2 and CO2 / CH4 were 27.8 and 47.5, respectively, significantly higher than their corresponding Knudsen diffusion selectivities of 0.8 and 0.6. This indicates that the prepared 0.5U ZIF-8 / 5% PSF composite membrane can achieve highly efficient CO2 separation. Figure 5X-ray diffraction characterization results of the selective separation composite membranes M1-M4 showed that the coating polymer solution and subsequent heating and drying processes did not affect the grain structure of ZIF-8. The intensity of the characteristic diffraction peaks of the composite membranes increased with increasing ZIF-8 concentration, which is attributed to the increased thickness of the ZIF-8 membrane layer. Table 1 shows the permeability and separation selectivity of the ZIF-8 polycrystalline membranes A1, A2, A3, A4 and the ZIF-8 / PSF selective separation composite membranes M1, M2, M3, M4 for equimolar CO2 / CH4 mixtures.
[0065] Table 1
[0066]
[0067] Example 2
[0068] Effect of polymer concentration on ZIF-8 / PSF selective separation composite membrane
[0069] Preparation method of ZIF-8 / PSF selective separation composite membrane: 0.5U ZIF-8 polycrystalline membranes were prepared according to Example 1, and the products were labeled A5, A6, and A7, respectively. These membranes were then inserted into polytetrafluoroethylene (PTFE) supports and coated with PSF solutions of concentrations of 2.5%, 5%, and 10%, respectively. After coating, the membranes were placed in a vacuum oven and heated at 150°C for 24 hours under vacuum, followed by natural cooling to room temperature. The resulting products were labeled M5, M6, and M7, respectively.
[0070] Characterization of ZIF-8 / PSF selective separation composite membrane: The CO2 / CH4 separation selectivity and permeability of the prepared product were measured (Table 2). With a fixed ZIF-8 precursor solution concentration of 0.5 U, the composite membrane prepared by coating with 5% PSF exhibited excellent CO2 permeability and CO2 / CH4 separation selectivity.
[0071] Table 2
[0072]
[0073] Example 3
[0074] Effects of coating different polymer solutions on ZIF-8 selective separation composite membrane
[0075] Preparation of ZIF-8 selective separation composite membranes: 0.5U ZIF-8 polycrystalline membranes were prepared according to Example 1, and the products were labeled as A8, A9, and A1, respectively. 10 PES and PSF particles were dissolved in N,N-dimethylformamide (DMF) solvent and stirred overnight. Pebax-2533 was dissolved in n-butanol solvent and heated in a water bath at 75°C for 5 hours to prepare a 5% polymer solution. The polymer was then sequentially coated onto products A8, A9, and A1 using a dip-coating method.10 On the surface, after coating, products A8 and A 10 The products were transferred to a vacuum oven and heated at 150°C for 24 hours under vacuum. Product A9 was then transferred to a vacuum oven and heated at 80°C for 12 hours under vacuum, and then allowed to cool naturally to room temperature. The resulting products were designated as M8, M9, and M... 10 .
[0076] Characterization of ZIF-8 Selective Separation Composite Membranes: The selective separation selectivity and permeability of the ZIF-8 / PES, ZIF-8 / Pebax-2533, and ZIF-8 / PSF selective separation composite membranes prepared above were determined. As shown in Table 3, the performance of the selective separation composite membranes varied considerably depending on the polymer coating. The ZIF-8 / PSF selective separation composite membrane exhibited the best CO2 / CH4 separation performance when coated with a 5% PSF polymer solution.
[0077] Table 3
[0078]
[0079] Example 4
[0080] ZIF-90 / PSF selective separation composite membrane and its preparation method
[0081] Preparation of ZIF-90 precursor solution: Zinc acetate dihydrate and imidazole-2-carboxaldehyde were dissolved in DMAc and deionized water, respectively. The zinc acetate solution was stirred in an ice bath, and the ligand solution was heated in a water bath at 80°C until the solution became clear, then cooled to room temperature. Zinc nitrate dihydrate solution was slowly added to the ligand solution, and the mixture was stirred until the solution became clear to obtain the precursor solution. The molar ratio of Zn, imidazole-2-carboxaldehyde, DMAc, and deionized water in the precursor solution was 1:2:36:93.
[0082] Preparation of ZIF-90 polycrystalline films: Three identical α-Al₂O₃ alumina supports (70 nm pore size) were immersed in a precursor solution for 30 seconds, then rapidly transferred to a 175°C forced-air oven and heated for 5 minutes, followed by natural cooling to room temperature. The ZIF-90 polycrystalline films were activated with methanol solvent for 2 hours, dried at room temperature, and the resulting products were designated as A. 11 A 12 A 13 .
[0083] Preparation of ZIF-90 / PSF selective separation composite membrane: The membrane was prepared by a dip-coating method on A... 11 A 12 A 13 The product surface is coated with a 5% PSF solution. After coating, it is placed in a vacuum oven and heated at 150°C for 24 hours under vacuum, then allowed to cool naturally to room temperature. The resulting products are denoted as M. 11 M12 M 13 .
[0084] Characterization of the ZIF-90 / PSF selective separation composite membrane: The ZIF-90 polycrystalline membrane A prepared above... 11 A 12 A 13 and ZIF-90 / PSF selective separation composite membrane M 11 M 12 M 13 The selectivity and permeability of the two-component gas separation were determined. As shown in Table 4, after coating with 5% PSF solution, the CO2 / CH4 separation performance of the ZIF-90 / PSF selective separation composite membrane was significantly improved compared with that of the ZIF-90 polycrystalline membrane.
[0085] Table 4
[0086]
[0087] Example 5
[0088] ZIF-7 / PSF selective separation composite membrane and its preparation method
[0089] Preparation of ZIF-7 precursor solution: Zinc nitrate hexahydrate and benzimidazole were dissolved in DMAc and deionized water, respectively. The zinc nitrate hexahydrate solution was then added to the ligand solution, and the mixture was stirred in an ice bath until the solution became clear, yielding the precursor solution. The molar ratio of Zn, benzimidazole, N,N dimethylacetamide (DMAc), and deionized water in the precursor solution was 1:2:72:185.
[0090] Preparation of ZIF-7 polycrystalline films: Three identical α-Al₂O₃ alumina supports (70 nm pore size) were immersed in a precursor solution for 30 seconds, then rapidly transferred to a 200°C forced-air oven and heated for 15 minutes, followed by natural cooling to room temperature. The ZIF-7 polycrystalline films were activated with methanol solvent for 2 hours and dried at room temperature. The resulting products were designated as A. 14 A 15 A 16 .
[0091] Preparation of ZIF-7 / PSF selective separation composite membrane: The membrane was prepared by a dip-coating method on A... 14 A 15 A 16 The membrane surface was coated with a 5% PSF solution, and then placed in a vacuum oven at 150°C for 24 hours under vacuum, followed by natural cooling to room temperature. The resulting products were denoted as M. 14 M 15 M 16 .
[0092] Characterization of the ZIF-7 / PSF selective separation composite membrane: The ZIF-7 polycrystalline membrane A prepared above... 14 A 15 A 16 and ZIF-7 / PSF selective separation composite membrane M 14 M 15 M 16 The selectivity and permeability of the two-component gas separation were determined. As shown in Table 5, after coating with 5% PSF polymer solution, the H2 / CO2 separation performance of the ZIF-7 / PSF selective separation composite membrane was significantly improved compared with that of the ZIF-7 polycrystalline membrane.
[0093] Table 5
[0094]
[0095] Example 6
[0096] ZIF-93 / Pebax-2533 selective separation composite membrane and its preparation method
[0097] Preparation of ZIF-93 precursor solution: Zinc acetate dihydrate and 4-methylimidazole-5-carboxaldehyde were dissolved in DMAc and deionized water, respectively. Then, zinc nitrate dihydrate solution was slowly added to the ligand solution, and the mixture was stirred in an ice bath until the solution became clear, yielding the precursor solution. The molar ratio of Zn, 4-methylimidazole-5-carboxaldehyde, DMAc, and deionized water in the precursor solution was 1:2:72:185.
[0098] Preparation of ZIF-93 polycrystalline films: Three identical α-Al₂O₃ alumina supports (70 nm pore size) were immersed in a precursor solution for 30 seconds, then rapidly transferred to a 200°C forced-air oven and heated for 15 minutes, followed by natural cooling to room temperature. The ZIF-93 polycrystalline films were activated with methanol solvent for 2 hours, dried at room temperature, and the resulting products were designated as A. 17 A 18 A 19 .
[0099] Preparation of ZIF-93 / Pebax-2533 selective separation composite membrane: Pebax-2533 was dissolved in n-butanol solvent and heated in a water bath at 75°C for 5 hours to prepare a 5% polymer solution. The membrane was then separated into A... 17 A 18 A 19 The product surface is coated with a 5% Pebax-2533 solution. After coating, it is placed in a vacuum oven and heated at 80°C for 12 hours under vacuum, then allowed to cool naturally to room temperature. The resulting products are designated as M. 17 M 18 M 19 .
[0100] Characterization of the ZIF-93 / Pebax-2533 selective separation composite membrane: The ZIF-93 polycrystalline membrane A prepared above... 17 A 18 A 19 With ZIF-93 / Pebax-2533 selective separation composite membrane M 17 M 18 M 19 The selectivity and permeability of the two-component gas separation were determined. As shown in Table 6, after coating with 5% Pebax-2533 solution, the CO2 / N2 separation performance of the ZIF-93 / Pebax-2533 selective separation composite membrane was significantly improved compared with that of the ZIF-93 polycrystalline membrane.
[0101] Table 6
[0102]
[0103] Analysis of Examples 1-6 demonstrates that the selective separation composite membrane preparation method provided by this invention is simple to operate and economical. A polymer solution is coated onto the surface of a zeolite imidazole ester framework polycrystalline membrane, which penetrates into the intercrystalline pores to form a through-structure selective separation composite membrane. The polycrystalline membrane layer, as the main channel for molecular transmembrane transport, exhibits excellent separation performance for various gas separation systems after being repaired by the polymer layer. It also possesses advantages such as short synthesis cycle, simple process, wide controllable range of synthesis conditions, high economic efficiency, and low energy consumption.
[0104] Unless otherwise defined, all terms, symbols, and other scientific terms used herein are intended to have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In some instances, terms having a conventional meaning are defined herein for clarification or ease of reference, and such definitions should not be construed as indicating a significant difference from conventional understanding in the art. The technical methods described or referenced herein are generally well understood by those skilled in the art and employed by conventional methods. Unless otherwise stated, the use of commercially available reagents and instruments shall be performed according to the manufacturer's instructions and parameters.
[0105] While the disclosure is as stated above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of this disclosure, and all such changes and modifications will fall within the protection scope of this invention.
Claims
1. A carbon dioxide gas selective separation composite membrane, characterized in that, The carbon dioxide gas selective separation composite membrane contains a zeolite imidazolium ester framework polycrystalline membrane and polysulfone PSF, wherein the polysulfone PSF fills the intercrystalline defects on the membrane surface of the zeolite imidazolium ester framework polycrystalline membrane. The zeolite imidazole ester framework polycrystalline film is formed by immersing the carrier in a precursor solution and treating it at high temperature, causing the solvent in the carrier to evaporate rapidly, driving the precursor solution to flow from the inside of the carrier to the outside and crystallizing and transforming inside and outside the carrier. A 5% PSF polymer solution is coated on the surface of the zeolite imidazole ester framework polycrystalline film. The PSF polymer solution penetrates into the intercrystalline pores to form a through-structure selective separation composite film. The zeolite imidazole ester framework polycrystalline film layer serves as the main channel for molecular transmembrane transport.
2. The carbon dioxide gas selective separation composite membrane as described in claim 1, characterized in that, The zeolite imidazole ester framework polycrystalline film is a ZIF-90 zeolite imidazole ester framework polycrystalline film.
3. A method for preparing the carbon dioxide gas selective separation composite membrane according to claim 1, characterized in that, Includes the following steps: S1: A precursor solution is obtained by mixing a metal salt, an organic ligand, a polar solvent, and water. The organic ligand is one of imidazole-2-carboxaldehyde, 2-methylimidazolium, 4-methylimidazolium-5-carboxaldehyde, benzimidazole, 5-methylbenzimidazole, 2-aminobenzimidazole, 4,5-dichloroimidazolium, and 2-nitroimidazolium. The metal salt is a zinc salt or a cobalt salt. The precursor solution is coated onto a support. The support coated with the precursor solution is heated at 200°C for 15 minutes and then cooled to allow the solvent in the support to evaporate rapidly. This causes the precursor solution to flow from the inside of the support to the outside and crystallize and transform inside and outside the support to form a zeolite imidazole ester framework polycrystalline film. S2: Immerse the zeolite imidazole ester framework polycrystalline film in a volatile solvent for 0.5 to 5 hours, and then dry it to obtain the activated zeolite imidazole ester framework polycrystalline film. S3: Polysulfone (PSF) is mixed with a polar solvent to obtain a PSF polymer solution with a mass fraction of 5%. The PSF polymer solution is coated onto the surface of an activated zeolite imidazole ester framework polycrystalline membrane by a dip-coating method. The membrane is then heated under vacuum at 150°C for 24 hours to allow the PSF polymer solution to penetrate into the intercrystalline pores, thereby obtaining a carbon dioxide gas selective separation composite membrane.
4. The preparation method according to claim 3, characterized in that, In step S1, the molar ratio of the metal salt, organic ligand, polar solvent and water is 1:(1-6):(50-150):(120-400).
5. The preparation method according to claim 3, characterized in that, The polar solvent in steps S1 and S3 is N,N-dimethylformamide or N,N-dimethylacetamide.
6. The preparation method according to claim 3, characterized in that, The metal salt is selected from one of zinc nitrate hexahydrate, zinc acetate dihydrate, or cobalt acetate tetrahydrate.
7. The preparation method according to claim 3, characterized in that, The support is selected from one of α-Al2O3 support, γ-Al2O3 support, and TiO2 support.
8. The preparation method according to claim 3, characterized in that, The volatile solvent is selected from one of methanol, ethanol, acetone, acetonitrile, and chloroform.
9. The preparation method according to claim 3, characterized in that, The organic ligand is 2-methylimidazole, the metal salt is zinc acetate dihydrate, the support is α-Al2O3 support, and the volatile solvent is methanol.
10. An application of the carbon dioxide gas selective separation composite membrane according to claim 1 or 2, characterized in that, The carbon dioxide selective separation composite membrane is used to separate carbon dioxide from a mixture of gases containing carbon dioxide and one or more of methane, nitrogen, and hydrogen.
Citation Information
Patent Citations
Zeolite imidazate framework polycrystalline film and preparation method thereof
CN116531972A
Oriented single-particle-layer MOF (Metal Organic Framework) composite film and preparation method thereof
CN116785951A
Hierarchical pore MOFs-on-SSN polymer composite membrane and preparation method thereof
CN118987990A
